Individualized quality of life benefit and cost-effectiveness estimates of proton therapy for patients with oropharyngeal cancer - Brodin, N. Patrik (Radiat Oncol, 2021)
BACKGROUND: Proton therapy is a promising advancement in radiation oncology especially in terms of reducing normal tissue toxicity, although it is currently expensive and of limited availability. Here we estimated the individual quality of life benefit and cost-effectiveness of proton therapy in patients with oropharyngeal cancer treated with definitive radiation therapy (RT), as a decision-making tool for treatment individualization. METHODS AND MATERIALS: Normal tissue complication probability models were used to estimate the risk of dysphagia, esophagitis, hypothyroidism, xerostomia and oral mucositis for 33 patients, comparing delivered photon intensity-modulated RT (IMRT) plans to intensity-modulated proton therapy (IMPT) plans. Quality-adjusted life years (QALYs) lost were calculated for each complication while accounting for patient-specific conditional survival probability and assigning quality-adjustment factors based on complication severity. Cost-effectiveness was modeled based on upfront costs of IMPT and IMRT, and the cost of acute and/or long-term management of treatment complications. Uncertainties in all model parameters and sensitivity analyses were included through Monte Carlo sampling. RESULTS: The incremental cost-effectiveness ratios (ICERs) showed considerable variability in the cost of QALYs spared between patients, with median $361,405/QALY for all patients, varying from $54,477/QALY to $1,508,845/QALY between individual patients. Proton therapy was more likely to be cost-effective for patients with p16-positive tumors ($234,201/QALY), compared to p16-negative tumors ($516,297/QALY). For patients with p16-positive tumors treated with comprehensive nodal irradiation, proton therapy is estimated to be cost-effective in ≥ 50% of sampled cases for 8/9 patients at $500,000/QALY, compared to 6/24 patients who either have p16-negative tumors or receive unilateral neck irradiation. CONCLUSIONS: Proton therapy cost-effectiveness varies greatly among oropharyngeal cancer patients, and highlights the importance of individualized decision-making. Although the upfront cost, societal willingness to pay and healthcare administration can vary greatly among different countries, identifying patients for whom proton therapy will have the greatest benefit can optimize resource allocation and inform prospective clinical trial design.